The Influence Of Authoritarian Parenting On Children's Personality - Harahap, Nur Hasanah; Nuramita, Nuramita; Putri, Adinda Eka; Waroh, Mona (International Research-Based Education Journal, 2024)
We really need to know that authoritarian parenting is a picture of parenting that disappoints parents so that children become obedient. authoritarian caregivers greatly influence children's social behavior, as the results of research conducted by Meike et al. that authoritarian parenting style has a bad effect, which means that the higher the authoritarian caregiver pattern set by parents for children, the lower the child's social behavior. This article was written using a literature study method that which sources come from various articles that match the title and what problems are discussed. The purpose of authoritarian parenting is to make them obedient by suppressing control by their parents. The guarantor uses authoritarian parenting, which is tough, inflexible, and will be taught to improve both in their environment, meaning that we can conclude that authoritarian parenting to the child's personality is very important for adapting children to the environment around them.